Adaptive Structural Model Development for Off-campus Student Housing Preferences using SEM – PLS Analysis - Mohd, Thuraiya; Johari, Noraini; Islamiah Abdullah Sani, Suwaibatul; Abdullah, Lizawati; Ahmad @ Mohamed, Nurulanis (International Journal of Engineering and Technology, 2019)
The immense number of student enrolment has created high demand for student accommodation far exceeding the available on-campus student accommodation provided by universities and colleges. Thus, some students may need to reside off-campus instead. As different groups of society have different preferences and needs, it is crucial to identify the off-campus student housing preferences who are the economically determinant group of people. This paper presents the formulation of a structural model depicting off-campus student housing preferences. The study presents data collected through a survey conducted via structured questionnaires in likert scale type of questions distributed randomly among off-campus students in selected public and private universities located within the State of Selangor. The data was analysed using the SEM – PLS. The results from analysis indicate that the four main factors to be considered relating to student housing preferences are: housing environment, location, housing quality, and housing accommodation. Findings of this research will provide a set of guidelines for off-campus student housing preferences that is significant to local authorities, housing developers, Higher Education Institutions (HEIs), students’ societies, and also the local communities to be the panacea for studentification issues.